Condition and current trends in the development of legal consulting services - Lukashov , Rostyslav (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
The article is dedicated to exploring the current state and trends in the development of legal consulting services. In writing the article, doctrinal and normative provisions on the researched issues have been analyzed. The article defines the concept of consulting service as an intellectual product that remains in the possession of the client after the consultation; it clarifies the essence of the category «legal services market»; it determines the specificity of the functioning of the regional legal services market, which is primarily oriented towards meeting the needs of the population; it characterizes the main reasons for the stagnation of the legal consulting services market. The author proposes actions to address the problems of the legal consulting services market in Ukraine, namely: highlighting the problems and prospects of the Ukrainian legal consulting services market; popularizing legal consulting services through conferences, books, brochures, compilations, booklets, etc., for end consumers as well as small and medium-sized enterprises; increasing the level of openness and transparency of the national legal consulting services market; forming and implementing educational courses to improve the qualifications of consultants in providing legal consulting services; supporting the activities of professional associations in the legal consulting services market.